TINJAUAN PEMANFAATAN PEMBERIAN BEASISWA BANTUAN KHUSUS MURID (BKM) PADA SISWA SMK NEGERI 1 PARIAMAN - 389-394 , Nidal Zuwida (Universitas Negeri Padang, 2014)
ABSTRACT Scholarship is a helpful effort that is given to students for helping them in fulfiling education cost during the study. In SMK N 1 Pariaman, one of the given scholarship to the underprivileged students is BKM scholarship. It is seen from the fact that the scholarship is often used for other necessity out of the educational needs. This research aims to know the BKM scholarship usage by observing 3 usage indicators , they are students’ school equipment purchase, transportation necessity of students and industrial work practices (Prakerin). This research uses descriptive method. The population of this research is students BKM scholarship recipients year 2013 in SMK 1 Pariaman as many as 177 students and the samples in this research are taken using proportional randomsampling technique with sample numbers as many as 63 students. The type of data in this research is primary data taken from recipients and secondary data taken form school archives concerning to the numbers of scholarship recipients. Data analysis technique is done by descriptive analysis using percentage formula and then translated into narrative form. This research result shows that BKM scholarship usage by students of SMKN1 pariaman viewed from 3 indicators. For purchasing the school equipment, the respondents’ answer is 63,6% or it can be categorized deficient. For students transportation needs, average answer is 57,2% or it can be categorized deficient and industrial work practices average answer is 64.0% or it can be categorized deficient. Keywords : Scholarship, BKM (Student Special Help)